Prevalence and associated factors of impaired kidney functions among children and adolescents in India: insights from the Comprehensive National Nutrition Survey (CNNS) 2016-18 - Angad Singh; Madhur Verma; Milan Das; Pragyan Paramita Parija; Saurabh Nayak; Vivekanand Jha (BMC, 2024)
Abstract Background Chronic kidney disease (CKD) is a significant public health problem. The burden of CKD in children and adolescents in India is not well described. We used data from the recent Comprehensive National Nutrition Survey (CNNS) to estimate the prevalence of impaired kidney function (IKF) and its determinants in children and adolescents between the ages of 5 and 19. Methods CNNS 2016-18 adopted a multi-stage sampling design using probability proportional to size sampling procedure after geographical stratification of urban and rural areas. Serum creatinine was tested once in 24,690 children and adolescents aged 5-19 years. The estimated glomerular filtration rate (eGFR) was derived using the revised Schwartz equation. The eGFR value below 60 ml/min/1.73 m2 is defined as IKF. Bivariate analysis was done to depict the weighted prevalence, and multivariable logistic regression examined the predictors of IKF. Results The mean eGFR in the study population was 113.3 + 41.4 mL/min/1.73 m2. The overall prevalence of IKF was 4.9%. The prevalence in the 5-9, 10-14, and 15-19 year age groups was 5.6%, 3.4% and 5.2%, respectively. Regression analysis showed age, rural residence, non-reserved social caste, less educated mothers, Islam religion, children with severe stunting or being overweight/obese, and residence in Southern India to be predictors of IKF. Conclusions The prevalence of IKF among children and adolescents in India is high compared to available global estimates. In the absence of repeated eGFR-based estimates, these nationally representative estimates are intriguing and call for further assessment of socio-demographic disparities, genetics, and risk behaviours to have better clinical insights and public health preparedness.